Objects as Mobile Processes - Hüttel, Hans; Kleist, Josva (BRICS Report Series, 1996)
The object calculus of Abadi and Cardelli [AC96, AC94b, AC94a] is intended as model of central aspects of object-oriented programming languages. In this paper we encode the object calculus in the asynchronous pi-calculus without matching and investigate the properties of our encoding.